A randomized controlled trial to determine the efficacy of a high carbohydrate and high protein ready‐to‐eat food product for weight loss. Issue 2 (19th January 2016) - Fuller, N. R.; Fong, M.; Gerofi, J.; Leung, L.; Leung, C.; Denyer, G.; Caterson, I. D.
Summary: Incorporating meal replacements has been shown to produce a significantly greater weight loss than a conventional reduced calorie diet. Ready‐to‐eat conventional foods may also be effective in this role and provide additional benefit because of their palatability, acceptance and enjoyment and thus increase dietary compliance. This trial investigated the efficacy of a ready‐to‐eat food product (Vita‐Weat biscuit) that is both high in carbohydrate and high in protein as part of a diet prescription for weight loss in an overweight and obese population group. A total of 76 participants were randomized to a 6‐week weight loss intervention including the ready‐to‐eat food product (intervention group) or advice on the 'Australian Guide to Healthy Eating' (control group). Both groups lost approximately 2 kg weight which equated to a reduction in body mass index of 0.70 kg m −2 . There was no significant difference in percentage weight loss from screening to 6 weeks between the two groups; mean difference for the intervention vs. control group: −0.20% (95% confidence interval: −0.96, 1.36); P  = 0.73. Both diets were nutritionally matched and well‐accepted over the 6‐week period. This study shows that the inclusion of a ready‐to‐eat food product can be included as part of a dietary programme to achieve a clinically significant weight loss over a short period. This may have benefit when incorporated into an individual's meal plan intermittently to assist weight control. It also provides support for current public health nutritional guidelines as the participants in this study following such advice were also successful in achieving a clinically meaningful weight loss.